2007
DOI: 10.1021/jf061864s
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Quercetin Activated Forms Involved in Antiradical, Antioxidant, and Prooxidant Biological Processes

Abstract: Quercetin, one of the most representative flavonoid compounds, is involved in antiradical, antioxidant, and prooxidant biological processes. Despite a constant increase of knowledge on both positive and negative activities of quercetin, it is unclear which activated form (quinone, semiquinone, or deprotonated) actually plays a role in each of these processes. Structural, electronic, and energetic characteristics of quercetin, as well as the influence of a copper ion on all of these parameters, are studied by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 49 publications
7
66
0
Order By: Relevance
“…In a previous study, it was shown that L-carnitine chelated ferrous ions (Fe 2þ ) through the carbonyl and hydroxyl functional groups [3]. Recently, Fiorucci and co-workers demonstrated that quercetin chelated metal ions in the same way [57].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was shown that L-carnitine chelated ferrous ions (Fe 2þ ) through the carbonyl and hydroxyl functional groups [3]. Recently, Fiorucci and co-workers demonstrated that quercetin chelated metal ions in the same way [57].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a single QU molecule is introduced into the cavity of b-CD at various positions with different orientations. The three possible orientations of QU are labelled by its rings (A, B, C) (Fiorucci, Golebiowski, Cabrol-Bass, & Antonczak, 2007) and are shown in Fig. 2a.…”
Section: Molecular Modelling Of Qu/b-cd-icmentioning
confidence: 99%
“…These free radicals polymerize to yield a mixture of complex metabolites. However, it seems that quercetin may act, in most of cases, after being metabolically activated (Metodiewa et al, 1999), and despite a constant increase of knowledge on both positive and negative biological effects of this natural product, it remains often unclear which activated form should play a role in a given process (Fiorucci et al, 2007). Indeed, semiquinone and quinone forms of quercetin, deriving from the abstraction of respectively one or two H•, are involved in many oxidative processes (Metodiewa et al, 1999;Gliszczynska-Swiglo et al, 2003;Hirakawa et al, 2002).…”
Section: Quinone and Semiquinone Formation During The Lipoxygenase Inmentioning
confidence: 99%
“…Indeed, semiquinone and quinone forms of quercetin, deriving from the abstraction of respectively one or two H•, are involved in many oxidative processes (Metodiewa et al, 1999;Gliszczynska-Swiglo et al, 2003;Hirakawa et al, 2002). For instance, quercetin reduces peroxyl radicals involved in lipid peroxidation, and through this reaction, a semiquinone species is produced, which then undergoes a disproportionation to generate a quinone form (Fiorucci et al, 2007). Three semiquinone forms for quercetin have been considered by Fiorucci et al (2008) in order to study the quercetin binding to lipoxygenase-3 by molecular modeling simulations.…”
Section: Quinone and Semiquinone Formation During The Lipoxygenase Inmentioning
confidence: 99%